IMPOLITENESS USED BY HATERS ON SOCIAL MEDIA (TAMADDUN NURI JURNALI, 2024)
The advent of social media has revolutionized the way individuals communicate, forming global platforms for dialogue, self-expression, and community building. Nonetheless, this digital landscape is marred by a darker vein of engagement, predominantly the rise of impoliteness and hate speech propagated by a subset of users frequently termed “haters”. This thesis aims to dissect the multifaceted nature of impoliteness within social media, examining its manifestation, the motivations of those who engage in such behavior, and the repercussions felt by targeted individuals. Through a combination of linguistic analysis and psychological frameworks, this research will unveil the mechanics behind the derogatory comments and aggressive interactions that pervade online spaces. Special attention will be given to the strategic use of impoliteness, ranging from blatant insults to the subtleties of sarcasm, and its potential function as a social tool or weapon. By delving into the psychological impact on recipients and the broader societal implications, this study seeks to offer a comprehensive understanding of online discourtesy.